Intellectual disability: Population-based estimates of the proportion attributable to maternal alcohol use disorder during pregnancy - O'Leary, Colleen; Leonard, H.; Bourke, J.; D'antoine, H.; Bartu, Anne; Bower, C. (Wiley-Blackwell Publishing Ltd., 2013)
Aim: The aim of this study was to examine the association between maternal alcohol use disorder and intellectual disability in children. Method: All mothers with an International Classification of Diseases (ICD) 9 and/or 10 alcohol-related diagnosis, a proxy for alcohol use disorder, recorded on the Western Australian health, mental health, and drug and alcohol data sets were identified through the Western Australian Data Linkage Unit (n=5614 non-Aboriginal; n=2912 Aboriginal). A comparison cohort of mothers without an alcohol-related diagnosis was frequency matched on maternal age within maternal Aboriginal status and year of birth of their children. Linkage with the Western Australian Midwives Notification System (1983–2001) identified all births to these mothers (n=10 664 and 7907 respectively). Linkage to the Western Australian Intellectual Disability Database and Register of Developmental Anomalies identified cases of intellectual disability with no identified genetic origin (intellectual disability) (n=1487) and fetal alcohol syndrome (n=66). Odds ratios (ORs) and 95% confidence intervals (CIs) for intellectual disability were calculated using logistic regression incorporating generalized estimating equations and used to estimate population-attributable fractions.Results: At least 3.8% (95% CI 2.84–4.89%) of cases of intellectual disability could be avoided by preventing maternal alcohol use disorder: 1.3% (95% CI 0.81–1.86%) in non-Aboriginal and 15.6% (95% CI 10.85–20.94%) in Aboriginal children. We observed a three-fold increase in the adjusted odds of intellectual disability in children of mothers with an alcohol-related diagnosis recorded during pregnancy (non-Aboriginal OR 2.89, 95% CI 1.62–5.18; Aboriginal OR 3.12, 95% CI 2.13–4.56), with a net excess proportion of 3.7% and 5.5% respectively. One-third (32%) of children diagnosed with fetal alcohol syndrome had intellectual disability. Interpretation: Maternal alcohol use disorder is the leading known risk factor for intellectual disability with no identified genetic origin.